EFEKTIVITAS TRICHOKOMPOS DIPERKAYA KELAKAI TERHADAP KEJADIAN PENYAKIT FUSARIUM PADA TANAMAN PADI: Effectiveness Of Trichocompost Fortened Kelakai To Fusarium Disease In Brown Rice Plant (Oryza nivara L - Mariana Mariana; Ismed Setia Budi; Nur Aini (Fakultas Pertanian Universitas Palangka Raya, 2022)
Brown rice is one of the local rice germplasm that is being developed in wetlands of South Kalimantan. One of the production constraints is Fusarium disease with symptoms of yellowing, drying and the plant will die. Biological control is a disease control solution to replace chemical fungicides which is not only economical but also environmentally friendly. This study aims to determine the effect of the application time of Trichokompos enriched Kelakai (Stenochlaena palustris) solution on fusarium disease in brown rice. The study was conducted in a greenhouse using the Completely Randomized Design method which consisted of four treatments, namely only inoculated with the pathogen, and three times of application of Trichoderma which was added with a solution of Kelakai namely one week before planting, at planting and one week after planting.. The Fusarium pathogen was isolated from the sacred brown rice plant. In the process of composting goat manure, Trichoderma sp. in rice media was added to produce Trikocompost. The results showed that the application of Trichokompos enriched with Kelakai solution was effective in controlling Fusarium disease in brown rice, both before planting, at planting and after planting. The effectiveness of the control began to decrease in the second week after application, the effectiveness value from 90.48% decreased to only 17.95% in the fourth week. Application of Trichokompos enriched Kelakai solution with various application times can extend the incubation period of the pathogen 16,20 days after inoculation compared to control 9,80 days after inoculation